Blends of L-tyrosine based polyurethanes for biomaterial applications (eXPRESS Polymer Letters, 2007)
Three polyurethane blends were made from segmented polyurethanes synthesized from desaminotyrosyl tyrosine hexyl ester (DTH), an L-tyrosine based diphenolic dipeptide, as chain extender. The soft segment of these polyurethanes is either polyethylene glycol (PEG) or polycaprolactone diol (PCL) and the diisocyanate is hexamethylene diisocyanate (HDI). The blends were developed to investigate the effect of varying composition on the overall physical, thermal, mechanical, surface and degradation properties of the material. The characterization results show that the properties of these blended materials can be controlled by adjusting the composition. Blends with increased PEG based polyurethane exhibited more water absorption and higher degradation characteristics. With increasing PCL based polyurethane, the mechanical properties of the blends were improved although the blends were relatively more amorphous in nature. The L-tyrosine based polyurethane blends hold the potential for use in different biomaterial applications.